KARAKTERISTIK FISIK-KIMIA KUALITAS AIR PADA LAHAN BEKAS TAMBANG BAHAN GALIAN GOLONGAN C DI KECAMATAN LANDASAN ULIN KOTA BANJARBARU - Dini Sofarini (Universitas Lambung Mangkurat, 2011)
Area of land miners in the area of Landasan Ulin district Banjarbaru town is diverse, while the excavation area C in the area of 25 hectares study. Results of the study of water quality, temperature, TDS, turbidity, salinity, pH and DO indicates that the value is still within normal limits on the allowed based on Water Quality Standards in government regulation No.82 of 2001 regarding management of water quality and Water Pollution Control. Value of normal water quality parameters showed that material excavated materials category C in Landasan Ulin district banjarbaru town is not harmful for biotic of water living in it.